Valuing Indigenous Rights Over Forest Governance in Six Asean Member Countries - Jamin, Mohammad (UUM Press, 2024)
Indigenous forests and indigenous communities have always shared a deep emotional, spiritual, and practical bond. This paper aims to methodically examine the relationship between the level of rights held by indigenous people concerning indigenous forest governance and the ability of the indigenous community in ensuring the long-term viability of its ecosystems. Concurrently, in examining and discussing these issues it is hoped that it can also contribute to the survival of the indigenous people in the future. The elucidation of indigenous people’s rights in the context of indigenous forest governance is based on the empirical scrutiny of the study hypotheses, utilizing the Sikor et al. type of rights. A quantitative analysis through Somer analysis was also carried out on the comprehensive secondary data sets obtained from six selected ASEAN member countries. The findings show that the six selected ASEAN member countries have not yet been granted the third level of rights for indigenous peoples with regard to indigenous forest governance. The statistical evidence strongly suggests the urgent need in these countries to grant indigenous people rights over indigenous forest governance, both within a legal framework and in practical implementation, particularly at the definitional and allocative level of rights. The absence of such rights at the highest levels raises significant concerns about the sustainability of indigenous forests and the welfare of indigenous people across the observed ASEAN member countries